Membangun Budaya Bersih Berkelanjutan Dan Penguatan Gotong Royong Dan Membuat Infrastruktur Bak Sampah Organik Dan Non- Organik, Plang Himbauan Sebagai Upaya Pelestarian Lingkungan - Ahmad Nur Ikhsan; Irfan Naufal Yuliansyah; Vistara Samudra Gupita; Nico Tasaka Putra; Evi Herlyaminda; Churin in; Hermawansa Hermawansa (Utami Publisher, 2026)
This community service initiative aims to transform collective behavior in maintaining environmental cleanliness to be more structured and sustainable. The main focus of this activity is to revive the spirit of mutual cooperation through concrete actions, namely the construction of waste disposal infrastructure that separates organic and non-organic waste, as well as the installation of strategic educational signs. The methods applied are participatory in nature, including the dissemination of information on domestic waste management, mass clean-up actions with residents, and the provision of physical sanitation facilities. The results of this program show significant changes in the aesthetics of the environment, which has become tidier, as well as the growth of critical awareness among the community in sorting waste at the source to support the long-term preservation of the local ecosystem.